Intermetallic Evolution for Isothermal Aging up to 2000 Hours on Sn-4Ag-0.5Cu and Sn-37Pb Solders with Ni/Au Layers - Azmah Hanim, Mohamad Ariff; Ourdjini, Ali; Saliza Azlina, Osman; Siti Rabiatull Aisha, Idris (Universiti Malaysia Pahang, 2013)
The reliability of a solder joint is closely related to the intermetallic compound formation during the joining process and its evolution after exposure to heat. Throughout this paper, interfacial reactions between Sn-4Ag-0.5Cu solders and Sn-37Pb solders with electroless nickel immersion gold (Ni/Au) surface finish were studied. The parameters include the solder type, thickness of the nickel layer and aging time. The results are focused on the type of intermetallic compound formed and the intermetallic thickness. Overall, aging changed the intermetallic morphology to become rounder, bigger and more compact with time. Aged Sn-4Ag-0.5Cu solders on Ni/Au exhibit the tendency for the intermetallic to change from (Cu,Ni)6Sn5 to (Ni,Cu)3Sn4 and finally Ni3Sn4. The results also showed that, with the parameters used in this experiment, a nickel thickness of 3µm is adequate to be a good diffusion barrier up to 2000 hours aging time. In Sn-37Pb, redeposition of (Au,Ni)Sn4 intermetallic starts after 500 hours until 2000 hours.